In-situ XANES and XPD studies of NiO/Ce0.9Zr0.1O2 IT-SOFCs anode nanomaterial as catalyst in the CPOM reaction - Zimicz, Maria Genoveva (2017)
The aim of this paper is to study the oxidation states of metal cations and the changes in the crystalline phases in NiO/Ce0.9Zr0.1O2 nanocatalysts under typical conditions of methane catalytic partial oxidation reaction by in-situ X ray absorption near edge spectroscopy (XANES) and X-ray powder diffraction (XPD) studies. The Ce0.9Zr0.1O2 mixed oxide was obtained by glycine-nitrate-combustion method, being the nickel incorporated by incipient wetness impregnation. The evolution of the crystalline structure with temperature and operating conditions was followed by in-situ XPD experiments and the oxidation states of Ce and Ni cations by in-situ XANES experiments at the Ce-LIII and Ni-K absorption edges. It was observed that NiO is completely reduced to Ni° at temperatures above 650 °C while Ce0.9Zr0.1O2 fluorite-like phase showed changes in lattice parameter due to cerium reduction and crystallite growth, but no phase transformations or segregations were observed. It was confirmed that Ni° is the active centre to activate methane molecule while Ce4+/Ce3+ ratio is strongly related with CO/CO2 concentration in the exhaust gas flow.